Princely Ambiguity: A Translation of Nikolaus of Modruš’ Funeral Oration for Cardinal Pietro Riario: Oratio in funere Petri Cardinalis Sancti Sixti (1474) - Brendan Cook; Jennifer Mara DeSilva (Royal Studies Journal, 2018)
This article provides an introduction to, and an English translation of, the Latin funeral oration written by Nikolaus, the bishop of Modruš (or Nicholas de Korto), on the occasion of Cardinal Pietro Riario’s death in January 1474. The article opens with a contextualizing introduction to the oration, its author, and its subject, as well as the contemporary late-fifteenth-century trend in publishing funeral orations. Following this introduction is an English translation from, and comparison with, Neven Jovanović’s openaccess, peer-reviewed Latin transcription (Croatiae Auctores Latini) and the British Library’s copy of the oration (ISTC No. in000488000), which was first printed in Rome in 1474 by Antonio and Raffaele Volterrano.